تصميم نظام منع تصادم ضبابي باستخدام مؤشر خطورة الهدف - Jolaha, Oulfat; Hanna, Jabr; Benshi, Qousay (Latakia University Journal -Engineering Sciences Series, 2019)
تصميم نظام منع تصادم ضبابي باستخدام مؤشر خطورة الهدف ألفت جولحة جبر حنا قصي بنشي يعدّ نظام منع التصادم المسؤول الأول عن أمان السفينة، حيث تقع عليه مسؤولية قرار المناورة في حال وجود هدف أو عائق على خط سير السفينة. إن المعرفة المسبقة لموقع التصادم يساعد كثيراُ في تجنب التصادم وبالتالي يزيد من أمان الإبحار، لذلك يستخدم مؤشر الخطورة للدلالة على احتمالية حدوث الاصطدام. يتم في هذا البحث تصميم نظام منع تصادم ضبابي باستخدام مؤشر الخطورة. وقد تم تجربة النظام بالمحاكاة في بيئة MATLAb. إن إدخال مؤشر الخطورة على نظام منع التصادم حسّن من أداء نظام منع التصادم الضبابي المقترح بشكلٍ واضحٍ. The collision prevention system is the primary responsible for the safety of the vessel, where it is responsible for maneuvering in case of a target or obstacle on the ship’s route. Pre-knowledge of the collision location greatly helps to avoid collision and thus increases the safety of navigation, so the hazard index is used to indicate the probability of collision. The collision prevention system is the primary responsible for the safety of the ship, where it is responsible for maneuvering in the event of a target or obstacle on the ship’s route. In this research, a fuzzy collision avoidance system is designed using a hazard indicator. The system has been simulated in the MATLAb environment. The introduction of the hazard indicator on the collision prevention system has improved the performance of the proposed fuzzy collision prevention system